사무직 근로자를 위한 사회인지이론 기반 걷기 프로그램의 효과 - 최혜영(Choi, Hye-Young); 양숙자(Yang, Sook-Ja) (Sŏngin Kanho Hakhoe chi, 2013)
Purpose: The purpose of this study was to examine the effects of a walking program for office workers in terms of social cognitive theory, walking activities and physiological indexes. Methods: A nonequivalent control group pretest-posttest design was used. The sample consisted of 50 office workers who were identified as having low levels of physical activity according to the International Physical Activity Questionnaire (IPAQ Research Committee, 2005). The participants were recruited from two companies in Seoul. Of the 50 participants, 26 were assigned to the non-equivalent experimental group and 24 to the control group. The walking program consisted of six didactic sessions via e-mail, two individual telecoaching sessions and three support group meetings over ten weeks. Data were analyzed using SPSS 17.0 program. Results: The non-equivalent experimental group reported significantly higher posttest scores in walking activities and adhering to the walking protocol than the control group. There were no differences in reported self-efficacy, outcome expectations, body mass index and blood pressure between the two groups. Conclusion: These findings indicate that a walking program based on social cognitive theory is effective in increasing physical activities for office workers.